2001
DOI: 10.1063/1.1348319
|View full text |Cite
|
Sign up to set email alerts
|

CN x /carbon nanotube junctions synthesized by microwave chemical vapor deposition

Abstract: The CNx/carbon nanotube junctions were successfully synthesized by microwave plasma-assisted chemical vapor deposition method from the mixture of N2/CH4 and H2/CH4 gases in a continuous growth process. High resolution transmission electron microscopy revealed that these junctions were of heterostructure between CNx nanotubes with polymerized nanobells and cylindrical carbon nanotubes. The growth process is quite simple and can be easily scaled up. The intimate correlation between the electronic structure and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 24 publications
4
54
1
Order By: Relevance
“…These proposals, based on a conception that the growth of a tube is catalyzed by single catalyst particle, can explain the formation of the type I bamboo-shape carbon nanotubes because, as mentioned above, only one catalyst particle exists at the end of this type of tubes. It should be pointed out that some authors found that the presence of nitrogen-containing gases (N 2 or NH 3 ) promotes the formation of bamboo-shape tubes [11], [12], [13], [22], [23] and [24], but our experimental results show that N 2 does not play a key role in their formation, at least in our reaction system. Although a large amount of N 2 is produced from the decomposition of PA and involved during the tube growth, normal tubes can be obtained under a similar N 2 -rich environment by controlling other experimental parameters.…”
Section: The Growth Of Bamboo-shape Cntscontrasting
confidence: 76%
See 1 more Smart Citation
“…These proposals, based on a conception that the growth of a tube is catalyzed by single catalyst particle, can explain the formation of the type I bamboo-shape carbon nanotubes because, as mentioned above, only one catalyst particle exists at the end of this type of tubes. It should be pointed out that some authors found that the presence of nitrogen-containing gases (N 2 or NH 3 ) promotes the formation of bamboo-shape tubes [11], [12], [13], [22], [23] and [24], but our experimental results show that N 2 does not play a key role in their formation, at least in our reaction system. Although a large amount of N 2 is produced from the decomposition of PA and involved during the tube growth, normal tubes can be obtained under a similar N 2 -rich environment by controlling other experimental parameters.…”
Section: The Growth Of Bamboo-shape Cntscontrasting
confidence: 76%
“…Until now, bamboo-shape nanotubes have been fabricated through various processes such as arc-discharge of graphite electrodes [1] and [2], pyrolysis of organometallic compounds [6] and [7], thermal chemical vapor deposition (CVD) [8] and [9], and plasma-enhanced CVD [10], [11], [12] and [13]. Some corresponding growth models have also been proposed [1], [2], [6] and [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the N-doped CNTs show n-type behavior regardless of a tube chirality. 9 Despite the great attention devoted to the N-doped CNT system, [10][11][12] some issues require further clarification. One is the electronic structure of the doped N atoms.…”
mentioning
confidence: 99%
“…4,5,7 Distinctively, a great part of the bamboo-like nano-structures consists of open ends of relatively short CNTs. 18,19,20 Individual short CNTs are weakly stacked one on top of the other to create a long nano-fiber. The observed bamboo-like structure along the nano-fiber length can be attributed to the integration of nitrogen into the graphitic structure, altering the nanotube surface from straight cylinder geometry.…”
Section: Optimized Carbon Nanotube Structuresmentioning
confidence: 99%